Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1995
DOI: 10.1111/j.1432-1033.1995.0641j.x
|View full text |Cite
|
Sign up to set email alerts
|

Induction of the Blood/Brain‐Barrier‐Associated Enzyme Alkaline Phosphatase in Endothelial Cells from Cerebral Capillaries is Mediated Via cAMP

Abstract: The mammalian bloodhain barrier is located at the endothelial cells of the cerebral capillaries. Alkaline phosphatase is associated to a very large extent with these cells and has been established as a marker enzyme for a differentiated bloodhain barrier phenotype in vivo and in vitro. Nevertheless cultured brain capillary endothelial cells (BCEC) lose this marker enzyme because of a cessation of de novo synthesis. Since astrocytes have been shown to possess the capability to re-induce the enzymic activity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Subsequent studies showed that astrocyte-derived signaling to CECs leading to increased expression of tight-junctions was mediated by, e.g., transforming growth factor beta (TGFβ), Sonic hedgehog and Wnt signaling (Siddharthan et al, 2007; Alvarez et al, 2011; Wang et al, 2018; Benz et al, 2019). Moreover, astrocytes regulate expression of alkaline phosphatase and Na-ATPase on CECs via cAMP and IL6, suggesting astrocytes regulate ionic homeostasis (Beuckmann et al, 1995; Sun et al, 1997).…”
Section: Established Principles: From the Bbb To The Neurovascular Unitmentioning
confidence: 99%
“…Subsequent studies showed that astrocyte-derived signaling to CECs leading to increased expression of tight-junctions was mediated by, e.g., transforming growth factor beta (TGFβ), Sonic hedgehog and Wnt signaling (Siddharthan et al, 2007; Alvarez et al, 2011; Wang et al, 2018; Benz et al, 2019). Moreover, astrocytes regulate expression of alkaline phosphatase and Na-ATPase on CECs via cAMP and IL6, suggesting astrocytes regulate ionic homeostasis (Beuckmann et al, 1995; Sun et al, 1997).…”
Section: Established Principles: From the Bbb To The Neurovascular Unitmentioning
confidence: 99%
“…The molecular mechanisms underlying TNAP function in the brain have been studied more thoroughly in neurons compared to BMECs. For an in-depth discussion of TNAP function in neurons, the reader is directed towards these excellent reviews [ 53 , 115 , 116 ]. A study from Deracinois et al was the first to show that inhibition of TNAP using a pan-AP inhibitor (levamisole) in bovine capillary endothelial cells (BCECs) increased cellular barrier permeability to Lucifer Yellow (Pe LY ) [ 74 ].…”
Section: Tnap In Brain Microvascular Endothelial Health and Functionmentioning
confidence: 99%
“…Several molecules such as retinol, cyclic AMP (cAMP), glucocorticoids, transforming growth factor-beta (TGF-β), interleukin-6 (IL-6), and basic fibroblast growth factor (bFGF) are known to modulate TNAP activity [ 33 ]. While retinol, cyclic cAMP, glucocorticoids, IL-6, and bFGF have been shown in previous studies to increase TNAP activity [ 115 , 116 , 121 , 122 ], TGF-β has been shown to suppress TNAP activity in brain ECs [ 122 ]. This non-exhaustive list of molecules highlights their potential importance in regulating TNAP function in brain ECs; however, the mechanisms through which these molecules modulate TNAP activity remain to be elucidated.…”
Section: Tnap In Brain Microvascular Endothelial Health and Functionmentioning
confidence: 99%
“…While most blood-brain barrier enzymes have been detected at the mRNA level, protein expression and activity of only few enzymes have been demonstrated. These include gamma-glutamyl transpeptidase (Beuckmann et al, 1995), alkaline phosphatase (Beuckmann et al, 1995), aromatic L-amino acid decarboxylase (Betz et al, 1980;Matter & Balda, 2003b), the phase I metabolising enzymes CYP1A1 (Filbrandt et al, 2004), CYP1B1 (Filbrandt et al, 2004), CYP3A4 (Ghosh et al, 2010;Ghosh et al, 2011), andCyp4x1 (Al-Anizy et al, 2006), NADPH-CYP P450 reductase (Chat et al, 1998;Ghersi-Egea et al, 1988;Minn et al, 1991;Ravindranath et al, 1990), epoxide hydrolase (Ghersi-Egea et al, 1988;Minn et al, 1991), and the phase II enzymes, 1-naphthol-UDP-glucuronosyltransferase (Ghersi-Egea et al, 1988) and GSTμ (Shang et al, 2008), and GSTπ (Bauer et al, 2008;Shang et al, 2008). The presence of these enzymes in the brain microvasculature indicates the existence of a metabolic barrier.…”
Section: Metabolic Enzymesmentioning
confidence: 99%